Supplier selection under a multi-sourcing strategy in a metalworking company - Mortara, Verónica Aída (2021)
To stay competitive, organizations need strategic and collaborative relationships with their supply chain. This research aims to design a method for supplier selection under a multi-sourcing environment. The proposed methodology combines the analytic hierarchy process and goal programming. The collaboration of the actors involved is essential for its application. The model selects the best combination of suppliers and the quantities to order from each one. It also allows systematizing the supplier selection process in accordance with the business strategy and competitive priorities.